IMMU-60. MAPPING TUMORAL AND IMMUNE HETEROGENEITY IN PD-1 RESPONSIVE GLIOBLASTOMA. (5th November 2018) - Losic, Bojan; Yong, Raymund; Akers, Nicholas; Laface, Ilaria; Tsankova, Nadejda; Sebra, Robert; Gnjatic, Sacha; Hormigo, Adilia
Abstract: Clonal evolution and the immune microenvironment in glioblastoma harbor critical clues to its known but poorly understood treatment resistance. To assess the potential benefit of immune checkpoint blockade (ICB) in glioblastoma it is critical to determine the immune interactions in the tumor microenvironment. We created a tumor-immune interaction map by computing the mutational and neo-epitope tumoral burden, along with the magnitude and clonality of infiltrating lymphocytes, from initial and recurrent tumor of a patient with a glioblastoma IDH1 wild type, unmethylated O 6 -methylguanine–DNA methyltransferase (MGMT) promoter who benefited from ICB. RNA sequencing was performed on samples from the primary and three spatial sectors of the recurrence. Data analyses included intra-tumoral gene expression including MHC-I allele-specific expression, expressed relative mutation, neo-epitope prediction, B/TCR profiling and correlation with analysis of immune cells by multiplex immunohistochemistry (MIHC). We found no evidence of hypermutation in the recurrence, a relative absence of immune infiltration in all recurrences despite the expression of a number of neo-epitope generating mutations (including a novel clonal mutation of EGFR), and compelling evidence of epigenetically driven aberrations in one sector of the recurrence. The differential tumor infiltrating lymphocyte burden observed between recurrent and primary biopsy, indicates immunosuppressive recurrent tumor microenvironment concurred by MIHC data that revealed a relative abundance of B-cell infiltrate. Neo-epitope editing (production) relative to primary is observed in 2/3 (1/3) recurrent tissues, consistent with relative somatic mutation overlap. Immune selection pressure induced from previous radiation/chemotherapy may be implicated in increased tumor heterogeneity and immune editing. Relative extended survival and response to ICB and VEGF-A inhibition can occur in IDH1 wild type, undetected MGMT and absent hypermutated phenotype GBM and warrant further studies to better determine the spectrum of response to PD-1 inhibition. Multi-regional analysis of recurrence may be give clues on failure of ICB.